2020
DOI: 10.1007/s00167-020-06172-5
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting and treated concomitant ankle instability does not compromise patient-reported outcomes of solitary osteochondral lesions of the talus treated with matrix-induced bone marrow stimulation in the first postoperative year: data from the German Cartilage Registry (KnorpelRegister DGOU)

Abstract: Purpose The purpose of this study was to compare the subjective ankle function within the irst year following matrixinduced bone marrow stimulation (M-BMS) of patients with a solitary osteochondral lesion of the talus (OCLT) with and without concomitant chronic ankle instability (CAI). Methods Data from the German Cartilage Registry (KnorpelRegister DGOU) for 78 patients with a solitary OCLT and a follow-up of at least 6 months were included. All patients received M-BMS for OCLT treatment. The cohort was subdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…22 Despite this, the impact of ankle stabilization on the outcome of OCLA surgery remains unclear. 11,15 A recent comparative study showed similar clinical outcomes in patients treated for OLT with and without chronic ankle instability, but increased failure rates and inferior performance in sports and recreational activities were observed in patients with instability. 23 The postoperative management and rehabilitation process for an ankle cartilage injury requires a multidisciplinary and comprehensive approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Despite this, the impact of ankle stabilization on the outcome of OCLA surgery remains unclear. 11,15 A recent comparative study showed similar clinical outcomes in patients treated for OLT with and without chronic ankle instability, but increased failure rates and inferior performance in sports and recreational activities were observed in patients with instability. 23 The postoperative management and rehabilitation process for an ankle cartilage injury requires a multidisciplinary and comprehensive approach.…”
Section: Discussionmentioning
confidence: 99%
“…12 The CTR working group of the DGOU published some observational studies based on data from the German Cartilage Registry (www.knorpelregister-dgou.de). 11,[13][14][15][16] As per one study, the surgical technique, postoperative care, and specific rehabilitation protocol might influence the outcome. The primary focus of rehabilitation after treating an OCLA should be returning to the pre-injury activity level.…”
Section: Introductionmentioning
confidence: 99%